Sustainability Values in Religious Education - Kondrla, Peter (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to identify opportunities for religious education in the field of promoting the values of sustainable development. By identifying key concepts, define options for future strategies in the implementation of sustainable development values in school teaching of religious education. Methods. The starting point is the analysis of the current religious education curriculum, which governs the teaching of religious education and is approved by both state and church authority. Based on the analysis, identify strengths and weaknesses and define potential areas within the curriculum where sustainability values can be applied. Results. The values of sustainable development and Christian values are based on a common anthropological platform, which is based on the dignity of the human person. Religious education should also be based on this platform. Conclusion. In order to apply the values of sustainable development, it is necessary to adjust the current curriculum in terms of content and scope of topics. At the same time, it is necessary to innovate in the way of training future teachers. The goal of innovations is the internalization of sustainability values within the value orientation of both teachers and students. Cognitive value. Christian values and the values of sustainable development are not in conflict. The content of the religious education curriculum has the potential to innovate its content to meet the current requirements of the United Nations (UN) agenda as well as the teachings of the Magisterium.